Tingkat Kognitif Soal Latihan Berdasarkan Taksonomi Timss Pada Buku Teks Matematika SMP/MTs Kelas VIII Kurikulum 2013 - Suyatno, Edy, Prof. Dr. Budi Murtiyasa. M.Kom, Dr. Maryadi, M.A (2016)
Exercises in mathematics textbooks generally have not been classified the cognitive level, resulting students difficulties in completing the exercises. Problems that have been classified according to the degree of cognitive allow teachers in defining its, questions and determining the cognitive level achieved by students and the students can complete their exercises gradually, from the easiest to hardest optimally. This study aims to analyze and describe the exercises mathematics textbooks of grade VIII SMP/MTs in curriculum2013 in terms of content domain assessment and cognitive domains in TIMSS. (1) The content of the numbers exercise are looked from level cognitive. (2) The content of the algebra exercise are looked from level cognitive. (3) The content of the geometry exercise are looked from level cognitive. (4) The content of the data content and opportunities exercise are looked from level cognitive. The research method of this study is literature, withen by reviewing the exercises and competency test exercises on the textbook. Furthermore, the exercises and test competencies are assessed, based on the content domain of numbers, algebra, geometry, data and opportunities and cognitive domains such as knowing, applying, and reasoning (Mullis et. Al., 2015). The findings of this reasearch is distribution levels of the cognitive for each aspect such as. (1) the content of numbers, distribution levels of the cognitive aspects of knowledge stands on largest positions 41.67%, mostly are contained of knowing which stands as the lowest level based on the cognitive level criteria. (2) the content of algebra, the distribution rate of cognitive aspects of the implementation stands on largest positions 61.01% for the first semester and 42.45% for the semester, mostly contains of applying (3) geometry content, distribution levels cognitive aspects of reasoning for 68.52% and 49.32% for the second semester of most of the exercises are reasoning. (4) The data content and opportunities, distribution of cognitive aspects of the implementation stands on largest positions 80.95% for the first semester, mostly contains of applying and for the first semester of the greatest aspects stands on reasoning positions 61.62%, most of the exercises reasoning.